Efektivitas Hemodialisa Berdasarkan Parameter Hemoglobin, Eritrosit, Dan Hematokrit Pada Penderita Gagal Ginjal Kronik - aini aini aini (Poltekkes Kemenkes Mataram, 2020)
Various diseases that cause kidney dysfunction that cause problems in the body such as the accumulation of metabolic waste, decreased hormone production that can cause chronic kidney failure. Hemodialysis is used to replace damaged kidney function, in patients with kidney failure who undergo hemodialysis will experience anemia (80-95%). This study aims to determine the effectiveness of hemodialysis in patients with chronic renal failure. This study uses an observational analytic method using primary data with a total sample of 30 respondents. This research was conducted in May at the Asy-Syifa Regional Hospital in West Sumbawa. Statistic test uses Wilcoxon because it is found that the data is not normally distributed, that is <0.05. The results of this study indicate that there is an increase in hemoglobin levels, hematocrit values, and the number of erythrocytes after hemodialysis.